Answer: Third option.
Explanation:
The distance between two points can be calculated with this formula:
![d=√((x_2-x_1)^2+(y_2-y_1)^2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jq23b7gn8a5hqb5oj8gmcxlbivj810cso4.png)
Then, given the points
and
, we can identify that:
![x_2=4\\x_1=6\\y_2=3√(2)\\y_1=5√(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fz38rkcpf78362pe4ok93o65djpmj59utg.png)
Now we must substitute these values into the formula:
![d=\sqrt{(4-6)^2+(3√(2)-5√(2))^2}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/oxw4sy1jj2ct5r4ywjjgprrwa5yv7hdb8a.png)
We get that the distance between these two points is:
![d=2√(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vkmugal3crrbvoxw4nmzr90kbkf1g7atui.png)